Corporate Tax Aggressiveness from Perspective: Capital Structure and Earning Management on Foreign Exchange Bank in Pandemic Era - Annisa Fitri Anggraeni; Winna Roswinna; Maria Lusiana Yulianti (Universitas Warmadewa, 2026)
Tax aggression is an illegal or legal tax planning activity with the aim of obtaining taxable profits through tax evasion or tax avoidance. This Research remains to measure Capital Structure and earning management are considered to be factors that influence the corporate tax aggressiveness. The research method used in this study is quantitative method. The unit of analysis is financial statements from 54 foreign exchange bank on pandemic era (2020-2023), with 216 samples, using panel data regression for hypotheses analysis. Capital structure has a positive influence but unsignificant on corporate tax aggressiveness because the data studied was in the pandemic period, when many banks suffered a significant decline in profits due to credit relief policies. Then, earning management also has a positive influence but unsignificant on the corporate tax aggressiveness, because Banking has become one of the most affected sectors of the pandemic, so banking companies feel no need to do earning management for tax evasion because they are losing condition. The results of the research, capital structure and profit management didn’t have a significant impact on corporate tax aggressiveness, as the government issued a tax harmonization law at the end of 2021 by lowering the corporate tax rate from 25% to 22%, so companies including banks felt no need to do tax planning because they had received special treatment from the government.